Applying a case management system to solve timeliness problem in international exchange of tax information - Koisin, Esther A.P. (2019)
The standard for international exchange of information for tax purposes developed by the Organisation for Economic Cooperation and Development (OECD) which Malaysia committed to implement in 2009 states that a request for information should be responded within 90 days from the date it is received. However, based on the OECD peer review assessment in 2014, less than 40% of the requests received by Malaysia were responded within the standard time in 2010 to 2012. Similar timeliness issues also appear for 2013 to 2018. This study aims at applying a Case Management System in the administration of the tax information requests (CMS-EOI) in the Inland Revenue Board of Malaysia (IRBM) which act as the Competent Authority for Malaysia to solve the timeliness issue. This study employs the action research method via the following method: select the action, take action to determine the features of the CMS-EOI and evaluate the consequences and result of the intervention to the timeliness problem. Data collection and analysis procedure are in accordance with the pragmatic approach by employing both quantitative and qualitative methods. The results revealed that after introducing the CMSEOI, an increase in percentage of requests were responded within the stipulated timeframe. Accordingly, this study benefits the IRBM both in finding a solution to a practical problem and in making a policy decision in improving work efficiency and effectiveness in managing the international exchange of tax information. This research findings contribute to the body of knowledge in terms of the application of action research method to find effective solution to a real timeliness problem within an organisation.